Beyond the stars : our origins and the search for life in the universe - Saraceno, Paolo (World Scientific, 2010)
What is the origin of the universe? Are we alone in the Universe? Using clear and plain language, the author explores these two interesting scientific-philosophical themes with a broad range of studies, including astronomy, cosmology, chemistry, biology.